Hubungan antara konsumsi protein dengan produksi, protein dan laktosa susu kambing Peranakan Ettawa - Galuh Estu Prihatiningsih; Agung Purnomoadi; Dian Wahyu Harjanti (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2015)
The study aimed to determine a correlation between crude protein intake, milk production, milk protein and milk lactose. This study used purposive sampling method. The sample used in this study were 35 Etawa crossbred goats with months of lactation 4-5 and lactation periods 2-3. Parameters observed were crude protein intake, milk production, milk protein and milk lactose. Data were analyzed using correlation analysis and simple linear regression. The result showed that crude protein intake, total milk production concentrations of milk protein and lactose were 0.77 kg/day; 0.30 kg/day; 0.196% and 3.32% respectively. There was a medium positive linear correlation between the crude protein intake with total milk production, protein and lactose content of milk. The correlation coefficient (r) were 0.258; 0.254 and 0,255 respectively. It could be concluded that the higher crude protein intake would increase the amount of milk production, protein and lactose contents. Keywords: crude protein intake, total milk production, milk protein, milk lactose